The Impact of the Food Price Crisis on Consumption and Caloric Availability in Pakistan : Evidence from Repeated Cross-sectional and Panel Data - Friedman, Jed (World Bank, Washington, DC, 2013)
Welfare losses from the 2008 food price crisis in Pakistan are deepening the gap between poor and non poor populations and further increasing inequality between the provinces. To estimate welfare losses, the reduction in caloric availability at household level is measured. The analysis of calorie intake by source supports the notion that rural households were shielded from the worst effects of the crisis by their capacity to grow their own food. Compensating variation estimates suggest that the average household would need 38 percent of its total precrisis expenditure to maintain precrisis consumption levels. The impact of the food price crisis (measured as the percentage of total expenditure required to restore consumption to the precrisis level) peaked at the end of 2008 to twice as high as at the start of the year. Average household caloric availability fell by almost 8 percent between 2006 and first half of 2008. Urban households were relatively worse off than rural households during the crisis. Income gains from sales of agricultural commodities produced by rural households presumably offset the negative impact of the food crisis to some degree. The drawdown of assets over 2008-10 was another important coping mechanism, especially for households without access to land.